Education and Training on Making Anti-Hypertensive Basil Jelly in The Area of Health Centre Rawat Inap Karya Wanita of Pekanbaru: Edukasi dan Pelatihan Pembuatan Jelly Kemangi Antihipertensi di Wilayah Puskesmas Rawat Inap Karya Wanita Pekanbaru` - Rahmi Pramulia Fitri; Dea Andarista; Monica Juliyanti; Putri, Veni Dayu; Rizka Febtrina (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Hypertension is a cardiovaskuler disease characterized by systolic blood pressure ≥140mmHg and diastolic blood pressure ≥90mmHg. Hypertension requires continuous management as it can lead to complications such as stroke and coronary heart disease. This community engagement activity was conducted at the Lembah Damai Subdistrict Health Center in Lembah Damai Village, Pekanbaru City in September 2023. The purpose of the activity is to empower participants by increasing their knowledge and skills in the non-pharmacological management of hypertension using basil plant. The engagement activity was carried out in several stages, including a focus group discussion (FGD), project awareness, educational sessions using a pre-post testing design, and training on making anti-hypertensive basil jelly. The instruments used in this community service activity include a knowledge questionnaire about hypertension and an observation sheet to assess partners’s skills in making antihypertensive basil jellt. The data analysis used is frequency distribution. The results of the engagement activity showed an increase in the average knowledge scores of the participants, from 69 (pre-test) to 90 (post-test), indicating an improvement in their understanding of hypertension. There was also an increase in the participants’s skills in processing and making anti-hypertensive basil jelly, from 20% (pre-test) to 100% (post-test). The engagement activity was successfully implemented, with pasticipants actively from beginning to end with enthusiasm.